Comparison of Photoelectrochemical Current in Amorphous and Crystalline Anodized TiO2 Nanotube Electrodes - Candy C. Mercado; Michael Eric L. Lubrin; Hazel Anne J. Hernandez; Reynaldo A. Carubio (International Journal of Photoenergy)
The interest in TiO2 nanotubes has resulted in a lot of studies including the effects of various parameters on the properties and performance for different applications. This study investigated the effect of anodization at a low temperature on the properties and photoelectrochemical performance. The effects of varied anodization settings on morphology, crystallinity, and PEC response were studied. Low-temperature anodization resulted in smaller pore diameter and shorter tube length. Annealing temperature affected the presence of varied phases of TiO2 such as the prominence of anatase and amounts of rutile and amorphous TiO2 at 125°C. To observe photoelectrochemical response, annealing at 450°C is necessary. However, a cathodic response was observed for TiO2 nanotubes synthesized with low voltage at low temperature. Hence, amorphous titania nanotubes annealed at 125°C with thickness achieved in the anodization can be a potential material used for photocatalytic applications due to its determined cathodic photoelectrochemical response.